A NOVEL SUPEROVULATORY PROTOCOL fOR ENHANCEMENT Of BOVINE IN VIVO EMBRYO YIELD - D. Reena; D. Gopikrishnan; S. Rangasamy; S. Balasubramanian (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The aim of this study was to evaluate two different superovulation protocols for quality embryo production. Donor animals were selected (Day 0) and a progesterone device was inserted. The superstimulatory treatment was initiated in day 7 (D7) with follicle stimulating hormone from porcine (FSHp) in eight decreasing doses each at 12 hours interval. Along with the fifth dose of FSHp, 500μg cloprostenol was administered. The progesterone device was removed 12h (Treatments P12) and 24 h after the first application of cloprostenol (Treatments P24). Twelve hours after the eighth dose of FSHp (D11) 25µg of Buserelin was administered and the inseminations were done after 12 and 24 hours. Embryos were collected in the forenoon of D18. P24 presented better results than the P12 treatment.